Thonningia sanguinea Extract: Antioxidant and Cytotoxic Activities Supported by Chemical Composition and Molecular Docking Simulations - Reda F. A. Abdelhameed; Sameh S. Elhady; Alaa Sirwi; Hanan Samir; Elsayed A. Ibrahim; Ama Kyeraa Thomford; Alaa El Gindy; Ghada M. Hadad; Jihan M. Badr; Mohamed S. Nafie (Plants, 2021)
The current study was designed to investigate the antioxidant and cytotoxic activities of Thonningia sanguinea whole-plant extract. The total phenolic content was determined using Folin–Ciocalteu reagent and found to be 980.1 mg/g, calculated as gallic acid equivalents. The antioxidant capacity was estimated for the crude extract and the phenolic portion of T. sanguinea, whereupon both revealed a dose-dependent scavenging rate of DPPH• with EC50 values of 36.33 and 11.14 µg/mL, respectively. Chemical profiling of the plant extract was achieved by LC-ESI-TOF-MS/MS analysis, where 17 compounds were assigned, including ten compounds detected in the negative mode and seven detected in the positive mode. The phenolic portion exhibited promising cytotoxic activity against MCF-7 and HepG2 cells, with IC50 values of 16.67 and 13.51 μg/mL, respectively. Phenolic extract treatment caused apoptosis in MCF-7 cells, with total apoptotic cell death 18.45-fold higher compared to untreated controls, arresting the cell cycle at G2/M by increasing the G2 population by 39.7%, compared to 19.35% for the control. The apoptotic investigation was further validated by the upregulation of proapoptotic genes of P53, Bax, and caspases-3,8 9, and the downregulation of Bcl-2 as the anti-apoptotic gene. Bcl-2 inhibition was also virtualized by good binding interactions through a molecular docking study. Taken together, phenolic extract exhibited promising cytotoxic activity in MCF-7 cells through apoptosis induction and antioxidant activation, so further fractionation studies are recommended for the phenolic extract for specifying the most active compound to be developed as a novel anti-cancer agent.